2019
DOI: 10.1111/ped.13755
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric oncologic emergencies: Clinical and imaging review for pediatricians

Abstract: Children with cancer are at increased risk of life-threatening emergencies, either from the cancer itself or related to the cancer treatment. These conditions need to be assessed and treated as early as possible to minimize morbidity and mortality. Cardiothoracic emergencies encompass a variety of pathologies, including pericardial effusion and cardiac tamponade, massive hemoptysis, superior vena cava syndrome, pulmonary embolism, and pneumonia. Abdominal emergencies include bowel obstruction, intussusception,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 79 publications
0
15
0
8
Order By: Relevance
“…Although not an intrinsically common complication, these mediastinal tumors can occasionally cause respiratory distress. In patients with respiratory distress whose bronchus is compressed by a mediastinal tumor, respiratory failure is likely to occur, especially when muscle-relaxant drugs are used for general anesthesia or mechanical ventilation [1]. Therefore, avoiding tumor biopsies for mediastinal tumors under general anesthesia has been recommended; the use of alternative diagnostic methods has also been advocated [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although not an intrinsically common complication, these mediastinal tumors can occasionally cause respiratory distress. In patients with respiratory distress whose bronchus is compressed by a mediastinal tumor, respiratory failure is likely to occur, especially when muscle-relaxant drugs are used for general anesthesia or mechanical ventilation [1]. Therefore, avoiding tumor biopsies for mediastinal tumors under general anesthesia has been recommended; the use of alternative diagnostic methods has also been advocated [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a series of infants with bacterial meningitis in the UK, 24% presented to the hospital >24 hours after symptom development8; this seemingly delayed presentation was associated with both increased mortality and neurologic morbidity 9. Other severe illnesses including stroke,10 11 malignancy12–14 and kernicterus15 16 can result in permanent injury and are also time-sensitive in terms of their need for definitive treatment. Furthermore, multiple jurisdictions in Canada, the USA and the UK have reported that children under 1 year of age are at greatest risk of death from medical conditions related to prematurity, congenital anomalies and infections with anywhere from 8% to 26% of deaths having some degree of preventability 8 17–19.…”
Section: Introductionmentioning
confidence: 99%
“…Early identification of illness in a community setting prior to hospital admission is the next logical extension of this paradigm and necessarily relies on family members to recognise and act on the evolving features of severe acute illness in their child. Family triggered activation of medical emergency teams is integrated into many paediatric hospitals25 26 and family assessment is acknowledged in the safety literature as paramount in illness recognition requiring urgent medical attention 13 27. In outpatient settings, symptom checklists,28 illness severity action plans29 and parent early warning scores30 have been described predominantly in selected populations with known disorders and more predictable symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Unresectable abdominal tumors could cause various complications as they enlarge. Bowel obstruction, bleeding, hydronephrosis, and jaundice due to compression of the biliary tract have been mainly reported [1][2][3] . Fistulizaton with the intestinal tract is a rare but serious complication in such tumors.…”
mentioning
confidence: 99%